2004
DOI: 10.1136/jnnp.2003.014993
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolic decreases related to the dose of the ApoE e4 allele in Alzheimer's disease

Abstract: Objectives: Declines in brain glucose metabolism have been described early in Alzheimer's disease (AD), and there is evidence that a genetic predisposition to AD contributes to accelerate this process. The epsilon4 (e4) allele of the apolipoprotein E (ApoE) gene has been implicated as a major risk factor in this process. The aim of this FDG-PET study was to assess the ApoE e4 dose related effect on regional cerebral glucose metabolism (METglc) in clinical AD patients, with statistical voxel based methods. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 35 publications
7
49
0
Order By: Relevance
“…E4(ϩ) subjects may have more global declines in CMRglc, as low rates were detected in other areas of the brain not seen in E4(Ϫ) subjects. 18 Thus, some differences may exist between E4 carriers in other regions of the brain or in progression of the CMRglc decline. 19 The molecular cause of the hypometabolism remains unclear.…”
Section: Glucose Metabolism In Admentioning
confidence: 99%
“…E4(ϩ) subjects may have more global declines in CMRglc, as low rates were detected in other areas of the brain not seen in E4(Ϫ) subjects. 18 Thus, some differences may exist between E4 carriers in other regions of the brain or in progression of the CMRglc decline. 19 The molecular cause of the hypometabolism remains unclear.…”
Section: Glucose Metabolism In Admentioning
confidence: 99%
“…As previously described, 20 all subjects underwent clinical and neuropsychological examinations to exclude organic brain disease and cognitive impairment.…”
Section: Controlsmentioning
confidence: 99%
“…In line with the strong and consistent results for APOE when using LOAD as the phenotype, most T-1 weighted MRI studies reported an association of APOE e4 with accelerated LOAD-related volume loss in the hippocampal region. [53][54][55][56] This is supported by several studies exploring the effect of the APOE e4 allele on glucose metabolism using FDG-PET, [57][58][59][60] or amyloid deposition using ([¹¹C] PiB-PET. [61][62][63] Few studies have examined the association between other genes and LOAD imaging measures, and most of these were GWAS studies.…”
Section: Genetic Variation and Neuroimaging Measures In Loadmentioning
confidence: 74%